Summary of the best evidence for prevention and management of frailty in elderly patients (老年患者衰弱预防及管理的最佳证据总结) - LIU Yi (刘艺); FAN Yaling (樊雅玲); WANG Ting (王婷); YOU Min (尤敏) (Journal of International Translational Medicine Limited, 2023)
Objective Relevant evidence of the prevention and management of frailty in elderly patients was retrieved, and the best evidence was formed after evaluation and summary, so as to provide reasonable and effective programs for the prevention or improvement of senile patients' debilitation. Methods A computer search was conducted on domestic and foreign databases and related websites to systematically search for relevant systematic reviews, guidelines, meta-analyses, expert consensus and evidence summaries related to the prevention and management of frailty in elderly patients. The search period is set to December 31, 2022. Results A total of 14 relevant literatures were included in this study. Specifically, it includes 6 systematic reviews/meta-analyses, 5 guidelines, 1 expert consensus and 2 evidence summaries. Finally, 7 evidence themes were formed, including identification and evaluation, systematic management, dietary intervention, exercise, medication management, multi-field intervention and continuous education, a total of 30 pieces of evidence. Conclusion This study summarizes the best available evidence on the prevention and management of frailty in elderly patients. Nursing staff should be careful to apply evidence to existing work, multidisciplinary team cooperation and combined with the patient's own situation to develop personalized prevention and management programs, so as to reduce the adverse effects of fateful state on patients' life and prognosis, promote the transformation of evidence into clinical practice. (目的 检索国内外老年衰弱患者预防及管理的相关证据, 评价与整合后形成最佳证据, 为预防或改善老年患者衰弱状态提供合理有效的方案。方法 使用计算机检索国内外数据库与相关网站, 系统地查找有关预防和管理老年患者衰弱的相关系统评价、指南、Meta分析、专家共识以及证据总结等。检索时限设定为建库至2022年12月31日。结果 最终共纳入相关文献14篇, 包括系统评价/Meta分析6篇, 指南5篇, 专家共识1篇以及证据总结2篇。最终形成了7个证据主题: 识别与评估、系统管理、饮食干预、运动锻炼、用药管理、多领域干预及延续化教育, 共30条证据。结论 本研究对目前预防和管理老年患者衰弱状态的最佳证据进行汇总。护理人员应慎重地将证据应用到现有的工作中, 多学科团队合作且结合患者自身情况制定个性化的预防及管理方案, 从而降低衰弱状态对患者生活和预后的不良影响, 推动证据向临床实践的转化。)